Transactions on Computational Science IX Special Issue on Voronoi Diagrams in Science and Engineering - Gavrilova, Marina L.; Tan, C. J. Kenneth.; Anton, Franȯis. (Lecture Notes in Computer Science,, 2010)
The 9th issue of the Transactions on Computational Science journal, edited by Franȯis Anton, is devoted to the subject of Voronoi diagrams in science and engineering. The 9 papers included in the issue constitute extended versions of selected papers from the International Symposium on Voronoi Diagrams, held in Copenhagen, Denmark, June 23-36, 2009. Topics covered include: divide and conquer construction of Voronoi diagrams; new generalized Voronoi diagrams or properties of existing generalized Voronoi diagrams; and applications of Voronoi diagrams and their duals in graph theory, computer graphics, bioinformatics, and spatial process simulation.